Rheological and Nutritional Properties and Sensory Evaluation of Bread Fortified with Natural Sources of Calcium - Amnah M. A. Alsuhaibani (Journal of Food Quality)
By-products of oyster shell and egg shell are new candidates for use as calcium supplements. The effect of the fortification of bread with natural sources of calcium such as skim milk powder, egg shell powder, and oyster shell powder at levels of 10%, 2%, and 2%, respectively, on the rheological, nutritional, and sensory properties was determined. Compared to the control bread, breads fortified with egg and oyster shells had a higher water absorption (%), dough development time, dough stability, mixing time, heat of transition, and setback viscosity but a lower weakening index. Skim milk-fortified bread had the lowest levels of carbohydrates and energy of the bread formulations tested. Oyster shell-fortified bread showed significantly higher contents of protein, ash, fibre, and carbohydrates. Sensory evaluation revealed that the breads fortified with egg and oyster shells showed lower scores for odour and general acceptability compared with the control bread and the bread fortified with skim milk powder. Higher levels of minerals and amino acids except proline were estimated in the tested breads. These results indicate that the addition of natural sources of calcium to bread could positively impact its technological and nutritional properties.